PERANCANGAN DESAIN ANTARMUKA WEBSITE MENTORY SEBAGAI PLATFORM PENGEMBANGAN SKILL PADA BIDANG INDUSTRI PARIWISATA DI PT. MADHAVA KREASI INDONESIA - Ni Wayan Diyarini; I Gede Arta Wibawa; I Made Widhi Wirawan (Jurnal Pengabdian Informatika, 2026)
The design of the Mentory website interface as a skill development platform in the tourism industry at PT. Madhava Kreasi Indonesia aims to enhance accessibility and quality of education for industry practitioners. Utilizing the Design Thinking method, the design process is carried out through five stages: empathize, define, ideate, prototype, and test. The outcome of this design is a user-friendly and responsive website that meets the needs of tourism industry practitioners in accessing training information. A well-designed interface plays a crucial role in creating a positive user experience, thus supporting competency development in this continually evolving industry.